Winning the long war retaking the offensive against radical Islam - Berman, Ilan (Rowman & Littlefield Publishers. Inc., 2009)
Winning the Long War is a timely, trenchant examination of the past seven years of the Global War on Terror, the future fronts that confront the United States in the struggle against radical Islam in the years ahead, and how America can reclaim the initiative in what has become the defining struggle of the twenty-first century